The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1152/japplphysiol.00178.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of muscle functional MRI data

Abstract: magnetic resonance imaging (mfMRI) is frequently used to determine spatial patterns of muscle involvement in exercising humans. A frequent finding in mfMRI is that, even within synergistic muscle groups, signal intensity (SI) data from individual voxels can be quite heterogeneous. The purpose of this study was to develop a novel method for organizing heterogeneous mfMRI data into clusters whose members behave similarly to each other but distinctly from members of other clusters and apply it in studies of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 29 publications
6
17
0
Order By: Relevance
“…Qualitatively, this finding is similar to that of Akima et al [19] in their study of intermittent isotonic dorsiflexion exercise and to that of our previous study of sustained isometric dorsiflexion at 40% MVC [18]. Moreover, this study demonstrates that this spatial heterogeneity is exercise intensity dependent, because it exists during contractions at 60% of MVC but not during contractions at 30% of MVC.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Qualitatively, this finding is similar to that of Akima et al [19] in their study of intermittent isotonic dorsiflexion exercise and to that of our previous study of sustained isometric dorsiflexion at 40% MVC [18]. Moreover, this study demonstrates that this spatial heterogeneity is exercise intensity dependent, because it exists during contractions at 60% of MVC but not during contractions at 30% of MVC.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, this study demonstrates that this spatial heterogeneity is exercise intensity dependent, because it exists during contractions at 60% of MVC but not during contractions at 30% of MVC. Finally, the findings confirm those of our previous study, in which we observed heterogeneity in the mfMRI SI time course during exercise but not following exercise [18].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations